Bacch. Fr. 63 M. – Commento - Tibiletti, Antonio (Collectanea Philologica, 2015)
This paper provides a commentary to Bacchylides’ fragmentum dubium 63 M. and off some further considerations about its interpretation. 1) The Muses, daughters of Mnemosyne, are the patrons of chant and present their sweet song to mankind. But few men have ever been gifted poetical knowledge, and the poet’s duty is to be their servant, herald and prophet: he must give their words voice and disclose, through Memory’s intervention, the past, present and future events. 2) Few other words are still readable: they seem to delineate a mythical conflict on horse or chariot. Which one?